the spatio-temporal distribution of fisheries resources along the coastal areas of Southern Iloilo, Philippines - Nochete, Charmane B (2023.)
The coastal areas of Southern Iloilo are characterized by multiple communities copeting for the same fishing areas and fisheries resources. conventional management measures such as Marine Protected Areas (MPAs) and seasonal closures were therefore implemented by the adjacent municicpalities to regulate fishing activities. This had consequently led to the criminalization of livehoods. With this, a total of 136ninformants from 16 coastal barangays were surveyed from June to November 2021 to solicit information on the spatio-temporal distribution of fishing activities were operated offshore, even beyond the 15 km municipal administrative boundary. Overlaps among fishing areas were documented. Pelagic species were mostly caught at the opposite end. The majority if the exploited species were reported to exhibit periodic abundance and migratory behavior brought about by the monsoons and tides. Each coastal municipality in the study site had distinctive bathymetry, substratum, and fisheries. Overall, there was no significant improvement in the availability, diversity, and affordability of fisheries resources resulting from the implementation of seasonal closures and MPAs. The fishing pattern in the study site indicated overinvestment with low low returns. Furthermore, the limited financial capacity of the fishermen to find new fishing grounds over long distances increased competition for fisheries resources along the gulf. It was conceivable that, unless fisheries policies are attuned to the behaviors of the fishermen and their exploited species, they will continue to be ineffectual.
Thesis (M.S. Fisheries Biology) -- Miagao, Iloilo : University of the Philippines Visayas, July 2023.